The Evolving Role of Extracorporeal In Situ Perfusion Technology in Organ Donor Recovery with Donation After Circulatory Determination of Death Organ Donors - Victoria R. Hammond; Marisa E. Franklin; Glen A. Franklin (Medicina)
The need for organs suitable for transplantation has continued to rise as need outweighs availability. Increased demand has driven innovation in the field. Over the past ten years, donation after circulatory death (DCD) donors have become a greater portion of the donor pool. This method of donation includes a period of warm ischemia time to the organs. Thus, its use is dependent on recovery methods. Historically, extracorporeal membrane oxygenation (ECMO) was one of the first pumping technologies to enhance organ preservation in the potential donor. Subsequently, the adoption of normothermic regional perfusion (NRP) technology has also shown promise in organ transplantation. These technologies have increased utilization of organs and enhanced the pool of donor organs. This review seeks to summarize the literature supporting in situ technologies (ECMO and NRP) utilized in procurement of solid organs from DCD donors. The benefit of in situ perfusion in DCD organ recovery is that these technologies increase the number of organs available for transplantation by reducing ischemic injury. The disadvantages include the added technical aspect, added operating room time, and the increased ethical concerns surrounding these technologies compared to conventional methods of organ recovery.